2022
DOI: 10.47372/ejua-ba.2022.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Ion Acoustic Waves in a Magnetized Quantum Plasma in the Presence of Exchange-Correlation Effects

Abstract: The nonlinear propagation of ion acoustic solitary waves are studied in a magnetized quantum plasma consisting of cold inertia ions and inertialless quantum electrons and positrons, including exchange-correlation effects., A Zakharov-Kuznetsov equation is derived by using the reductive perturbation method. The effects of quantum plasma parameters on the propagation characteristics of the ion acoustic solitary waves have been investigated. It is found that the phase velocity, amplitude and width of the solitary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…They found that the quantum DIAWs is significantly affected by cylindrical geometry. Recently, Khaled et al [27] have investigated the nonlinear propagation of ion acoustic waves in a quantum electron-positron-ion plasma, in the framework of Zakarov-Kuznetsov equation, including the influence of electron/positron exchange-correlation effect. To the best of our knowledge there is no detailed investigation about the propagation of DIAWs in a 2D cylindrical quantum dusty plasma consisting of inertialess degenerate electrons and positrons, inertial ions and negatively charged dust particles, including quantum electron/positron exchange-correlation effects.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the quantum DIAWs is significantly affected by cylindrical geometry. Recently, Khaled et al [27] have investigated the nonlinear propagation of ion acoustic waves in a quantum electron-positron-ion plasma, in the framework of Zakarov-Kuznetsov equation, including the influence of electron/positron exchange-correlation effect. To the best of our knowledge there is no detailed investigation about the propagation of DIAWs in a 2D cylindrical quantum dusty plasma consisting of inertialess degenerate electrons and positrons, inertial ions and negatively charged dust particles, including quantum electron/positron exchange-correlation effects.…”
Section: Introductionmentioning
confidence: 99%